Facilitated containment and winding for pain management in preterm infants: randomized crossover clinical trial (Research, Society and Development, 2022)
This study aimed to analyze the effectiveness of the effects of facilitated restraint and wrapping to reduce pain in premature newborns. A quantitative approach was carried out, in line with the assumptions of an experimental study of the crossover, randomized clinical trial type. Considering the analyzes based on the duration of the painful procedure, changes in heart rate, respiratory rate and oxygen saturation, and the organization according to the subsystems of autonomous, motor and behavioral states of the newborn, it was shown that there was no statistically significant difference between the facilitated restraint and wrapping interventions. However, in the period of application of facilitated restraint, an earlier physiological and behavioral stability was observed, which promoted reorganization, decreased agitation and hemodynamic changes, compared to wrapping. Facilitated containment is performed by positioning the hands, simulating the fetal position. While wrapping consists of keeping the neonate's limbs flexed and the neonate's hands close to the face, an adequate thoracic excursion must be ensured, a position that must be maintained by wrapping the premature's body in tissues, bands or swaddling clothes, which has the function of offering greater safety during the painful procedure. This study revealed efficacy in non-pharmacological interventions, facilitated restraint and wrapping, demonstrating their importance in pain management during procedures that cause low-intensity pain sensitivity in newborns.